2021
DOI: 10.1016/j.breast.2021.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer survivorship care during the COVID-19 pandemic within an urban New York Hospital System

Abstract: To examine clinicodemographic determinants associated with breast cancer survivorship follow-up during COVID-19. Methods: We performed a retrospective, population-based cohort study including early stage (Stage I-II) breast cancer patients who underwent resection between 2006 and 2018 in a New York City hospital system. The primary outcome was oncologic follow-up prior to and during the COVID-19 pandemic. Secondary analyses compared differences in follow-up by COVID-19 case rates stratified by ZIP code. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“… Breast cancer patients receiving NET can be managed safely by adopting the same way as patients with similar tumours treated with a surgery-first approach. Mo et al, USA 106 Retrospective, population-based cohort study 1 Mar 2019–1 Dec 2020 2942 (NR) Follow-up after resection of stage I/II breast cancer during COVID-19 situations Only 42% of patients attended follow-up during the pandemic. Patients being younger, with lower socio-economic status, and previously taking adjuvant radiotherapy were more likely to participate in the follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Breast cancer patients receiving NET can be managed safely by adopting the same way as patients with similar tumours treated with a surgery-first approach. Mo et al, USA 106 Retrospective, population-based cohort study 1 Mar 2019–1 Dec 2020 2942 (NR) Follow-up after resection of stage I/II breast cancer during COVID-19 situations Only 42% of patients attended follow-up during the pandemic. Patients being younger, with lower socio-economic status, and previously taking adjuvant radiotherapy were more likely to participate in the follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that breast cancer survival rates decline if follow-up care is not fully re-established. 106 …”
Section: Resultsmentioning
confidence: 99%
“…Globally, there has been a large disruption to BC services during the pandemic [32], and the current study coincides with this trend. Previous research found that follow-up BC visits decreased by about half from 2019 to 2020 [10].…”
Section: Discussionmentioning
confidence: 95%
“…To reduce the risk of COVID-19 for BC patients, diagnostic and surgical procedures were delayed, treatment plans changed, and routine follow-up visits postponed [6][7][8]. Across a number of countries, studies have shown that many BC patients experienced a change in their recommended treatment during the pandemic [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation